Wilms tumor gene 1 (WT1), TP53, RAS/BRAF and KIT aberrations in testicular germ cell tumors - Boublíková, Ludmila; Bakardjieva-Mihaylova, Violeta; Škvárová Kramarzová, Karolína; Kuzilkova, D; Dobiasova, A; Fišer, Karel; Stuchlý, Jan; Kotrová, Michaela; Büchler, Tomáš; Dusek, P; Grega, Marek; Rosová, Blanka; et al. (Cancer letters, 2016)
PURPOSE: Wilms tumor gene 1 (WT1), a zinc-finger transcription factor essential for testis development and function, along with other genes, was investigated for their role in the pathogenesis of testicular germ cell tumors (TGCT). METHODS: In total, 284 TGCT and 100 control samples were investigated, including qPCR for WT1 expression and BRAF mutation, p53 immunohistochemistry detection, and massively parallel amplicon sequencing. RESULTS: WT1 was significantly (p < 0.0001) under-expressed in TGCT, with an increased ratio of exon 5-lacking isoforms, reaching low levels in chemo-naïve relapsed TGCT patients vs. high levels in chemotherapy-pretreated relapsed patients. BRAF V600E mutation was identified in 1% of patients only. p53 protein was lowly expressed in TGCT metastases compared to the matched primary tumors. Of 9 selected TGCT-linked genes, RAS/BRAF and WT1 mutations were frequent while significant TP53 and KIT variants were not detected (p = 0.0003). CONCLUSIONS: WT1 has been identified as a novel factor involved in TGCT pathogenesis, with a potential prognostic impact. Distinct biologic nature of the two types of relapses occurring in TGCT has been demonstrated. Differential mutation rate of the key TGCT-related genes has been documented.
Keywords: mutace; Tumor Suppressor Protein p53; Neoplasms, Germ Cell and Embryonal; Phenotype; Feasibility Studies; protoonkogenní proteiny B-raf; Cell Line, Tumor; mutační analýza DNA; testikulární nádory; High-Throughput Nucleotide Sequencing; geny ras; Immunohistochemistry; lidé; Testicular Neoplasms; DNA Mutational Analysis; Mutation; genetická predispozice k nemoci; Genes, ras; germinální a embryonální nádory; Genetic Predisposition to Disease; WT1 Proteins; imunohistochemie; Proto-Oncogene Proteins B-raf; retrospektivní studie; protoonkogenní proteiny c-kit; Down-Regulation; prospektivní studie; studie proveditelnosti; Male; nádorové biomarkery; Prospective Studies; vysoce účinné nukleotidové sekvenování; proteiny WT1; nádorový supresorový protein p53; Proto-Oncogene Proteins c-kit; Biomarkers, Tumor; down regulace; fenotyp; mužské pohlaví; Retrospective Studies; kvantitativní polymerázová řetězová reakce; nádorové buněčné linie; Real-Time Polymerase Chain Reaction; Humans